Resource allocation mechanism for multiuser multichannel cognitive radio networks - Maharaj, Bodhaswar Tikanath Jugpershad (University of Pretoria, 2018)
Cognitive radio (CR) technology has been considered one of the most promising solutions to make the best potential use of the scarce spectrum resources in next generation wireless communication. Because of the stringent limitations on the utilization of the radio resources in a cognitive radio network (CRN), the available resources are usually scarce and dynamic. Developing appropriate mechanism to construct allocation protocols for CRN that can assign the resources in a fair and efficient manner to diverse users with different features is essential to achieve the promise of the CR technology in reality and worth studying. “The mechanism for resource allocation protocol design in CRN” describes the topic of this research work and the contents of this thesis are organized around it. Before investigating how to design appropriate mechanism for CR resource allocation (RA) protocols, the model of the radio resource and the model of how a CR system utilizes the resource have to be clarified. In this thesis, by a comprehensive study of the relevant literatures, the modeling of critical components of a CR system and the theory behind it are identified and investigated. The existing protocols are also analyzed to address the limitations and gaps in the design of allocation protocols. An important feature, if not the most, that the allocation protocol for the CRN should possess is the ability to adjust the strategy of RA when the circumstances that affect the data transmission of the CR system varies, such as the activity of the license users or the variety of CR users’ demands. According to such considerations, the mechanism, namely distribution probability matrix (DPM), is designed to guide and describe the channel allocation protocol quantitatively. To testify how this mechanism works, the protocols based on the DPM, together with reference protocols in a multichannel CRN, are analyzed by a queuing model. The numerical results shows the flexibility and adaptability that the protocols based on the DPM can achieve. Another important function of the DPM mechanism is the potential to describe complex protocols with specific principles and to help design protocols aimed at specific objectives. To demonstrate this, a maximum throughput (MT) protocol that is aimed at maximizing the overall throughput of the CR system in a multi-user multi-channel scenario is structured using the DPM mechanism. The existing reference protocols, including maximum rate and random allocation, are described under the DPM mechanism as well as the MT protocol. All the protocols are implemented in a multiuser multichannel CRN and analyzed by a queueing analytical framework proposed by the author that is capable of acquiring the performance metrics of each CR user independently with efficiency. Numerical results show that the MT protocol is able to outperform the existing protocol in terms of the overall throughput of the CRN. The last problem identified and addressed in this thesis is to investigate the potential of specific performance metrics that a CR system can achieve under certain conditions with the help of the DPM mechanism. An optimization problem that is aimed at maximizing the overall weighted throughput of a multi-user multi-channel CRN under the delay constraint is formulated and solved using the DPM mechanism. The key factors that affect the optimal weighted throughput and the optimal allocations are investigated through the numerical results obtained by the proposed queueing analytical framework. The advantages of the DPM mechanism in optimizing the performance of CRN is also revealed by the formulation and solution of the optimization problem. The RA protocol is the essential kernel to address the RA problem in the CRN context. This thesis, by providing an objective and effective mechanism that works as a universal tool to describe and evaluate the RA protocols, succeeds in making effective contribution to addressing the RA problem in the CRN and further, helping the CR technology realize its meaningful promises.